The application of entransy theory in heat transfer optimization of heat exchanger networks and multi-stage latent heat storage systems - Zhang, Xiangzhi (2018)
Under the pressure of energy deficiency and the greenhouse effect, thermal energy recovery and recycling is of significant importance for the sustainable development of society. Various theories and technologies have been employed to enhance the performance of thermal energy systems. Entransy is a physical quantity to characterize the potential energy of heat transfer. Entransy theories including entransy dissipation extremum and entransy-dissipation-based thermal resistance have been widely used in heat transfer enhancement and heat exchangers optimization. The foundation of entransy theory is based on a hypothesis that heat transfer can be described as the transport of thermomass. In this thesis, the entransy theory was elaborated systematically, and the conservation equations of thermomass transport and heat transfer momentum were derived. After that, the new concepts of exothermic potential and endothermic potential were proposed to describe the heat exchange potential as a supplement to entransy theory. A pinch-analysis-based method was adopted to optimize the design of heat exchanger networks (HEN) in a chemical production process. In this approach, the pinch was identified using entransy dissipation minimization. Then, heat exchangers and heating/cooling utilities were organized around the pinch. It is shown that the retrofitted HEN reached a better heat recovery, meanwhile the energy consumption of auxiliary utilities was reduced. Later on, entransy dissipation minimization was applied to the optimization of a multi-stage PCM thermal energy storage system for heat exchange with heat transfer fluid (HTF). The system is constituted with several heat exchanger units in series, and the PCM in each unit has different phase transition temperature. Entransy dissipation minimization and entropy generation minimization were employed respectively to optimize the stage number (n), the number of transfer units (NTU), and PCM phase transition temperatures. In heat storage process, the results showed that, under the condition of fixed inlet/outlet HTF temperatures, entransy dissipation minimization leads to higher average storage temperature, and therefore better heat recovery performance. Similarly, in cool/cold storage process, entransy dissipation minimization also showed a superiority over entropy generation minimization. It can be concluded that entransy theory is applicable in the heat transfer optimization of HEN and multi-stage PCM thermal energy storage system. However, experimental validations need to be done in the further research to make the designs available in practice.